PEWARISAN KULTUR KEDAERAHAN BETAWI MELALUI SINERGI MASYARAKAT ADAT DAN PEMERINTAH DAERAH - Retno Wulandari, Putri Ayu; Ridho, Kholis; Sabina, Marsya Kayla; Ramadhani, Salsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Betawi culture grew from a blend of diverse ethnicities and developed into a distinctive identity for the people of Jakarta. Religious, social, and cultural values are passed down through daily practices such as religious study groups, pilgrimages, cooperation, and traditional arts and culinary activities. This research explores how the Betawi communities persevere to maintain their cultural roots in the era of modernization. Reinforcement from various parties, including the government and traditional community leaders, in Betawi communal activities has become a cultural habituation that is not only personified in the form of symbols, but also in cultural practices that grow from life values that continue to be carried out across generations. The support of the local government through the Jakarta Fair (PRJ) from 1968 until now has been an affirmation of state policy to strengthen the continued survival of Betawi culture. This preservation also indicates that Betawi identity is not merely a cultural heritage, but a life practice that adapts to various social transformations.